Indian industrial worker - Sharma, Baldev Raj. (Delhi, 1974)
This book is the outcome of an intensive study of an automo bile factory in India as part of my doctoral research. The study was conducted in the mid-sixties and formed part of a four-nation research project on the automobile worker under the overall direc tion of Professor William H. Form of Michigan State University, the other nations being Argentina, Italy and the United States. Although the study formed the basis of my Ph.D. dissertation submitted in 1967, this book is substantially different from the dissertation. The conceptual framework and some of the empirical data are no doubt taken from the thesis but here the similarity ends, for the book goes beyond the dissertation in at least three significant ways. First, the review of literature of the many topics treated in the book stretches far beyond its coverage in the disser tation. Secondly, the findings of the study have been compared with a much larger number of studies undertaken both before and after the thesis was submitted. And, finally, there is a more detail ed treatment of the implications for future research as also for managerial action. In writing this book I have drawn liberally from my teaching as well as research experience of the last six years at the Indian Institute of Management, Ahmedabad.
Keywords: Economics